ANALISIS KESANTUNAN BERBAHASA DALAM BUKU AJAR CERDAS BERBAHASA INDONESIA UNTUK KELAS X SMA/MA KARANGAN ENGKOS KOSASIH - Wijayanti, Wenny (Widya Warta, 2017)
This research was to describe (1) the linguistic politeness and (2) the kind of politeness shift in Cerdas Berbahasa Indonesia untuk SMA/MA Kelas X written by Engkos Kosasih. This research used descriptive-qualitative research design. The data of the research were descriptive; they were the form of utterances and sentences stated in each sections of the handbook. The result of the research was that there were 219 utterances which obeyed and violated the politeness principles. 152 utterances obeyed the politeness principles especially the tact maxim. 15 utterances were the polite imperative utterances but they violated the modesty maxim. The forms of violations found in the handbook were 50 utterances with the modesty maxim violation, while the other 2 utterances with the modesty maxim violations and at once the tact maxim violations. Most utterances found in the handbook obeyed the politeness principles. It seems that the imperative utterances in the handbook are polite.